2020
DOI: 10.1016/j.jsxm.2020.05.032
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Cohort Study Evaluating Surgical Aptitude Over Time in a New Male-To-Female Penoscrotal Vaginoplasty Program

Abstract: Background Given the burgeoning demand for gender affirmation surgery, there are few studies examining both surgical process variables and patient outcome variables. Knowing the learning curve for surgical teams who are beginning to perform this procedure will be important for patient safety and presurgical patient counseling as more institutions open transgender surgical programs. Aim The purpose of this study was to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(37 citation statements)
references
References 19 publications
1
36
0
Order By: Relevance
“…Post-operative wound infection rates range from 0% to 27%. 15,20,22,[24][25][26][27]30,34 COVID-19 induces respiratory-predominant multiorgan dysfunction, including myocardial, renal, enteric and hepatic dysfunction, which coincides with the tissue expression of ACE2. 3 Meanwhile, several studies have shown that ACE2 is expressed in human testes (eg spermatogonia, Leydig cells and Sertoli cells), 4,5 suggesting that the testes may be another organ affected by COVID-19.…”
Section: Wound Infectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Post-operative wound infection rates range from 0% to 27%. 15,20,22,[24][25][26][27]30,34 COVID-19 induces respiratory-predominant multiorgan dysfunction, including myocardial, renal, enteric and hepatic dysfunction, which coincides with the tissue expression of ACE2. 3 Meanwhile, several studies have shown that ACE2 is expressed in human testes (eg spermatogonia, Leydig cells and Sertoli cells), 4,5 suggesting that the testes may be another organ affected by COVID-19.…”
Section: Wound Infectionmentioning
confidence: 99%
“…Ferrando and Whynott did not find an association between surgeon experience and complications that occurred in the immediate postoperative period; the authors postulated that early complications are "common and inherent" to the procedure. 24,27 Most studies show that the rate of serious complications following vaginoplasty is low and comparable to complications of other genitourinary reconstruction surgeries. 17,19,23,24 Reported rates of adverse intraoperative complications, such as rectal or genitourinary injury or need for intraoperative blood transfusion, range from 1.5% to 2.6%.…”
Section: Complic Ations Following Vag Inopl a S T Ymentioning
confidence: 99%
See 3 more Smart Citations